Effectiveness of additional follow-up telephone counseling in a smoking cessation clinic in Beijing and predictors of quitting among Chinese male smokers. (December 2015) - Wu, Lei; He, Yao; Jiang, Bin; Zuo, Fang; Liu, Qinghui; Zhang, Li; Zhou, Changxi; Liu, Miao; Chen, Hongyan; Cheng, KK; Chan, Sophia; Lam, Tai
Abstract Background No previous studies have investigated whether additional telephone follow-up counseling sessions after face-to-face counseling can increase quitting in China, and whether this strategy is feasible and effective for promoting smoking cessation is still unclear. Methods A non-randomized controlled study was conducted in Beijing. We compared the quit rates of one group which received face-to-face counseling (FC) alone (one session of 40 min) to another group which received the same face-to-face counseling plus four follow-up sessions of brief telephone counseling (15–20 min each) at 1 week, 1, 3 and 6 month follow-up (FCF). No smoking cessation medication was provided. From October 2008 to August 2013, Chinese male smokers who sought treatment in a part-time regular smoking cessation clinic of a large general hospital in Beijing were invited to participate in the present study. Eligible male smokers (n  = 547) were divided into two groups: FC (n  = 149) and FCF (n  = 398). Main outcomes were self-reported 7-day point prevalence and 6 month continuous quit rates at 12 month follow-up. Results By intention to treat, at 12 month follow-up, the 7-day point prevalence and 6 month continuous quit rates of FC and FCF were 14.8 % and 26.4 %, and 10.7 % and 19.6 % respectively. The adjusted odds ratios (95 % confidence intervals) of quitting in FCF compared to FC was 2.34 (1.34–4.10) (P  = 0.003) and 2.41 (1.28–4.52) (P  = 0.006), respectively. Stepwise logistic regression showed that FCF, being married, unemployed and a lower Fagerström score were significant independent predictors of 6 month continuous quitting at 12 month follow-up. Conclusions Using systematically collected data from real-world practice, our smoking cessation clinic has shown that the additional telephone follow-up counseling sessions doubled the quit rate.